The role of melatonin in the light of current knowledge - Algiert, Barbara; Rotsztejn, Helena; Mucha, Paulina; Trznadel-Grodzka, Ewa (Dermatology Review/Przegląd Dermatologiczny, 2016)
Recent studies have shed new light on the role of melatonin. Local tissue synthesis has been investigated. A special system responsible for the synthesis and metabolism of melatonin has developed in the human skin. The primary role of melatonin is the regulation of circadian rhythms, but studies have demonstrated the diversity of its activities. Potent antioxidant action of melatonin in the skin is emphasized. The skin has developed a specific antioxidant melatoninergic system which protects against oxidative stress. Presence of melatonin metabolites in the skin confirms its strong antioxidant properties. Melatonin has the ability to restore the physiological balance between synthesis and degradation of extracellular matrix proteins by induction of heme oxygenase in murine fibroblasts irradiated with UVR. There is a hypothesis concerning the participation of melatonin in etiology of vitiligo. Disturbances of melatonin skin synthesis and dysregulation of its receptors may explain the pathogenesis of disease.